2022
DOI: 10.1101/2022.03.12.484072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-histone protein methylation inTrypanosoma cruziepimastigotes

Abstract: Post-translational methylation of proteins, which occurs in arginines and lysines, modulates several biological processes at different levels of cell signaling. Recently, methylation has been demonstrated in the regulation beyond histones, for example, in the dynamics of protein-protein interaction and protein-nucleic acid. Mass spectrometry-based proteomics has allowed a large-scale identification of protein methylation - mainly in arginine residues -, in different organisms, including some trypanosomes. Howe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…While the conditions used in our immunoprecipitations did not allow us to assess methylation, nine of the proteins identified in our pulldowns were methylated in T. cruzi epimastigotes. Most of these shared proteins were involved in translation ( Table 2, bold italics ) (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the conditions used in our immunoprecipitations did not allow us to assess methylation, nine of the proteins identified in our pulldowns were methylated in T. cruzi epimastigotes. Most of these shared proteins were involved in translation ( Table 2, bold italics ) (28).…”
Section: Resultsmentioning
confidence: 99%
“…First recognized for modifying histones, it is now clear that SET domain PKMTs can catalyze methylation of many non-histone substrates including tumor suppressors, proteins involved in signaling pathways and translation, and transcription factors (6). In the single study of protein lysine methylation in trypanosomes, methylated lysine residues were identified in proteins related to translation, stress response, glycolytic processes, amino acid transport, and cellular metabolism (7) . The role that SET domain PKMTs play in kinetoplastid biology, especially through the modification of non-histone proteins, is unknown.…”
Section: Introductionmentioning
confidence: 99%